Dynamic effects in the response of offshore wind turbines supported by jackets under wave loading. (1st July 2017) - Wei, Kai; Myers, Andrew T.; Arwade, Sanjay R.
Highlights: Assess the dynamic effects in the response of OWT jackets under wave loading. Consider wave regularity and three example OWT jackets. Present results of the dynamic amplification factor for the OWT jackets. Discuss the effects of wave height, structural period, etc. on the dynamic amplification. Abstract: This paper studies the effect of structural dynamics on the response of an offshore wind turbine (OWT) supported by a jacket and subjected to wave loads. The study includes a series of time-domain dynamic analyses based on loading from regular and irregular wave histories and three example OWT support structures. The OWT support structures are proportioned to collectively span a broad range of the first fundamental period of an OWT supported by a jacket. For each dynamic analysis, a representative static analysis is also considered, and a dynamic amplification factor (DAF) is calculated and discussed as a function of wave height, wave regularity, and structural period. The results demonstrate that dynamic effects may amplify the structural response significantly for loading caused by smaller waves, but the amplification is minimal for loading caused by large waves, which have longer periods and, for the jacket geometry considered here, cause large wave-in-deck forces. For the specific scenarios and models considered in this paper, the structural period is found to have a small influence on the DAF.